PENGARUH OPINI AUDIT, PERGANTIAN MANAJEMEN, UKURAN KANTOR AKUNTAN PUBLIK (KAP), AUDIT FEE, DAN UKURAN PERUSAHAAN KLIEN TERHADAP AUDITOR SWITCHING (Studi Empiris pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017) - Vinta, Lovika; Yuneita, Anisma; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to analyze the influence of Audit Opinion, Change ofManagement, KAP Size, Fee Audit, and Firm Size to Auditor Switching. Thesampling method used in this study was purposive sampling. Population of thisstudy is a Service Companies Listed on the Indonesian Stock Exchange Period2013 -2017 and obtained 18 companies as samples, in the 5 year time period from2013 to 2017 amounted to 90 companies. Hypothesis in this research are tested bylogistic regression analytical method using the Product and Service Solutions(SPSS) version 22.0 for windows. The results of this research indicate thatvariable Audit Opinion and Change of Management has no effect to auditorswitching while variable KAP Size, Fee Audit, and Firm Size has an effect toauditor switching. Keywords : Auditor Switching, Audit Opinion, Change of Management, KAPSize, Fee Audit, and Firm Size